ANALYSIS OF DAMAGE TO AIRCRAFT PARTS MADE OF TITANIUM ALLOYS AND INCREASE OF THEIR WEAR RESISTANCE BY GAS-THERMAL COATINGS - Khimko, Andrii; Mikosianchik, Oksana; Mnatsakanov, Rudolf; Bespalov, Serhii; Tokaruk, Vitalii (Problems of Friction and Wear, 2025)
The damage analysis of aircraft parts made of titanium alloys is carried out. Damage resulting from cyclic loads in the form of wear is shown. Gas-thermal coatings based on nickel for protection and restoration of parts made of titanium alloys are analyzed. The results on fretting resistance of some coatings that were applied by plasma method are carried out. It is established that the most fretting-resistant are coatings based on ВK, as well as a molybdenum coating. It is theoretically determined that with an increase in temperature in the friction zone, the logarithmic decrement of the molybdenum coating increases more than that of nickel-based coatings. It is established that due to the high hardness of the ВK type coating, it is possible to protect titanium parts of high rigidity, where the main operational factor is friction. In cases where wear of parts is combined with other loads such as bending, torsion, stretching, the optimal choice will be a molybdenum coating on parts made of titanium alloys.